Inequalities in Income, Labor, and Education: The Challenge of Inclusive Growth - Jose Ramon G. Albert; Jesus C. Dumagan; Arturo Jr. Martinez (Philippine Institute for Development Studies (PIDS), 2015)
While economic growth is important for poverty reduction, the rather stellar performance of the Philippines in economic growth has still not translated into reduction of poverty. This is in large part due to issues pertaining to distribution. Inequalities in income, as well as inequities in labor and education, have provided barriers for everyone to participate in growth processes. The study looks at trends in various statistics on poverty and income distribution, and then examines how disparities in opportunities across rural/urban areas, between the sexes, and between the poorest and richest segments of society in labor and education have prevented the country from reducing poverty. It also examines why the conditional cash transfer program can provide opportunities toward more social and economic inclusiveness.
Keywords: 330; poverty; inequality; Philippines; inclusive growth